Glucocorticoid receptor modulators decrease alcohol self-administration in male rats. (1st May 2021) - McGinn, M. Adrienne; Tunstall, Brendan J.; Schlosburg, Joel E.; Gregory-Flores, Adriana; George, Olivier; de Guglielmo, Giordano; Mason, Barbara J.; Hunt, Hazel J.; Koob, George F.; Vendruscolo, Leandro F.
Abstract: Alcohol use disorder (AUD) is associated with the dysregulation of brain stress and reward systems, including glucocorticoid receptors (GRs). The mixed glucocorticoid/progesterone receptor antagonist mifepristone and selective GR antagonist CORT113176 have been shown to selectively reduce alcohol consumption in alcohol-dependent rats. Mifepristone has also been shown to decrease alcohol consumption and craving for alcohol in humans with AUD. The present study tested the effects of the GR modulators CORT118335, CORT122928, CORT108297, and CORT125134 on alcohol self-administration in nondependent (air-exposed) and alcohol-dependent (alcohol vapor-exposed) adult male rats. Different GR modulators recruit different GR-associated transcriptional cofactors. Thus, we hypothesized that these GR modulators would vary in their effects on alcohol drinking. CORT118335, CORT122928, and CORT125134 significantly reduced alcohol self-administration in both alcohol-dependent and nondependent rats. CORT108297 had no effect on alcohol self-administration in either group. The present results support the potential of GR modulators for the development of treatments for AUD. Future studies that characterize genomic and nongenomic effects of these GR modulators will elucidate potential molecular mechanisms that underlie alcohol drinking in alcohol-dependent and nondependent states. Highlights: Alcohol use disorder is associated with a dysregulated brain glucocorticoid system. Glucocorticoid receptor (GR) modulators can have varying effects on GR-regulated activity. CORT118335, CORT122928, and CORT125134 reduced alcohol self-administration in alcohol-dependent and nondependent rats. These results support the potential use of GR modulators for AUD treatment.